Blended programs for working professionals: developing a path analysis-based structural model to achieve skill development outcomes. (17th May 2019) - Kumar, Ranjan; Pande, Neerja
Blended learning has emerged as a promising alternative to traditional classroom-based programs for working professionals, faced with rapid skill obsolescence and constraints of time and location. The present study focuses on this mixed-mode format, combining face-to-face and online learning and targets working professionals as the learner segment. Four notable contributions follow. One, the paper establishes a multi-disciplinary framework comprising learner-centric, pedagogical andragogical and institutional factors as the key pillars of a successful blended learning program. Two, the paper creates taxonomy of cause-effect-based empirical studies and identifies predictor, mediator and dependent constructs. Three, the paper evaluates 44 identified constructs and chooses six of them - active learning, intrinsic motivation, perceived quality, perceived value, perceived organisational support, self-regulated learning - by following a rigorous analytical procedure. And finally, the paper develops a structural model, specifying path relationships between the chosen constructs and skill development.